IMPROVING SAFEFRUITS AND VEGETABLES (SF&V) SUPPLY CHAIN IN HANOI - Thi Thanh Huyen, Nguyen; Thi Xuan Huong, Nguyen (Journal of Forestry Science and Technology, 2017)
Producing, trading and consuming safe vegetables and fruits is a hot and necessary issue of the social life. In this trend, safe vegetable supply chain studies would be meaningful in resolving problems. The article focuses on the difficulties of safe fruit and vegetable supply chains and looking for a solution to improve the efficiency of the chain. The current supply chain for SF&V is unsustainable because of some reasons that are loose linkage between factors, confusing market mechanism, difficulties in traceability and breach of commitment in quality and food hygiene and safety, etc. In order to develop SF&V supply chain in Hanoi, the above problems need to be solved thoroughly by a number of solutions that are targeted at each factor in the chain and concentrate on solving key constraints of these factors. These solutions should be completing the chain’s structure; raising awareness of the whole society as well as of factors about SF&V; fulfilling institutions and policies related to production and consumptionSF&V; advertising, popularizing and propagating widely to people about processes, effects and images of safe vegetables and solving problems of traceability, etc.